Dirofilaria causing eye infection in a patient from Malaysia - Mahmud, Rohela; Ibrahim, Jamaiah; Hui, T.T.; Mak, J.W.; Ithoi, Init; Amirah, A. (SEAMEO Regional Tropical Medicine and Public Health Network, 2009)
Human dirofilariasis caused by Dirofilaria immitis and Dirofilaria repens have been reported in Malaysia. This is the fourth reported case of dirofilariasis caused by D. repens. The patient was a Chinese male from Kuching Sarawak, Malaysia who presented with a one day history of redness and itchiness over the temporal aspect of his left eye. A worm was seen and later removed from beneath the conjunctiva under local anesthesia and based on the morphological characteristics, it was identified as an immature Dirofilaria repens.